Perceptual consequences of change in vocoded speech parameters for various reverberation conditions - Drgas, Szymon; Błaszak, Magdalena (Archives of Acoustics, 2007)
The perceptual consequence of change in parameters of vocoded speech for various reverberation conditions has been examined. The three controlled variables were: number of bands, instantaneous frequency changes rate and reverberation conditions. The effects were quantified in terms of: (a) non-words’ recognition scores for young normal-hearing listeners, (b) “ease of listening” based on the time of reaction (response delay) and (c) the subjective measure of difficulty (ten-degree scale). The results have shown that the fine structure information is a relevant cue in speech perception in reverberation conditions. It has also been observed that only the slow variations of instantaneous frequency are critical in perception. A good correlation between all subjective measures considered was found in this study.